Sediment echosounder raw data (IXblue Echoes 10000 working area dataset) of the Lagoon of Orbetello, images and profiles - Brocard, Gilles; Vitale, Quentin; Jouve, Guillaume; Darras, Lionel; Benech, Christophe; Mattio, Laurent; Goiran, Jean-Philippe (PANGAEA, 2024)
Sub-bottom profiles were acquired in the lagoon of Orbetello in 2021 and 2022 using an Exail Echoes 10000 profiler, in water depths of 1.0 to 1.5 m. The surveys allowed successful imaging of lagoon layers and its underlying substrate, down to depth of 15 m. The Echoes 10000 was mounted on a pole attached to a boat provided by the Fishermen's Cooperative of Orbetello (Cooperativa Pescatori di Orbetello). The surveys were made possible owing to a scientific and technical collaboration between the French CNRS, via the Archéorient laboratory (university of Lyon 2) and the Exail (Ixblue) company. It was funded by project IDEX Thalassocracies without Port and by project Labex IMU Intelligence of Urban Worlds - Urbo. The goal of these surveys was to understand how the triple tombolo of Orbetello has formed, and how the lagoon has developed in between the two outer tombolos in Holocene time. Data include 46 profiles, provided as jpg images, SEG-Y and CHP files generated from processed XTF files handled using the Delph Geo acquisition and interpretation software (Exail).
Keywords: Echoes 10000; images; Lagoon; Orbetello; sub-bottom profiles